2000
DOI: 10.1074/jbc.275.12.8531
|View full text |Cite
|
Sign up to set email alerts
|

Recruitment of a Foreign Quinone into the A1 Site of Photosystem I

Abstract: Electron paramagnetic resonance (EPR) and electronnuclear double resonance studies of the photosystem (PS) I quinone acceptor, A 1 , in phylloquinone biosynthetic pathway mutants are described. Room temperature continuous wave EPR measurements at X-band of whole cells of menA and menB interruption mutants show a transient reduction and oxidation of an organic radical with a g-value and anisotropy characteristic of a quinone. In PS I complexes, the continuous wave EPR spectrum of the photoaccumulated Q ؊ radica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
53
0

Year Published

2000
2000
2011
2011

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 85 publications
(58 citation statements)
references
References 42 publications
(53 reference statements)
5
53
0
Order By: Relevance
“…This quinone, which may be identical to the plastoquinone-9 identified on the basis of the solvent extraction studies described here, may substitute for phylloquinone in the A 1 site, thereby promoting electron transfer to F X and F A /F B . Spectroscopic evidence supporting the presence of plastoquinone-9 in the A 1 site and its participation in forward electron transfer is provided in the second paper of this series (33).…”
Section: Discussionmentioning
confidence: 99%
“…This quinone, which may be identical to the plastoquinone-9 identified on the basis of the solvent extraction studies described here, may substitute for phylloquinone in the A 1 site, thereby promoting electron transfer to F X and F A /F B . Spectroscopic evidence supporting the presence of plastoquinone-9 in the A 1 site and its participation in forward electron transfer is provided in the second paper of this series (33).…”
Section: Discussionmentioning
confidence: 99%
“…Q-band EPR Spectroscopy of Photoaccumulated PS I Complexes-CW EPR spectrometry at 34 GHz was carried out using the same instrumentation and methods described previously (14).…”
Section: Figmentioning
confidence: 99%
“…Time-resolved EPR Spectroscopy at X-and Q-band-Transient EPR spectra and pulsed EPR spectra were performed according to methods described previously (14,21).…”
Section: Figmentioning
confidence: 99%
See 1 more Smart Citation
“…31,35 An examination on these mutants showed that PS I of S. PCC6803 recruited plastoquinone molecules in the menA or menB gene inactivated mutants, 31,36 or 2-phytyl-1,4-naphthoquinone in the menG gene inactivated mutant 35 than PhQ. It was previously reported that PS I of a euglenophyceae Euglena gracilis and a cyanobacterium Synechococcus sp.…”
Section: Menaquinone-4 In Ps I Of C Caldariummentioning
confidence: 99%